Exact Analytic Formula for Conductance Predicting a Tunable Sommerfeld–Arrhenius Thermal Transition within a Single‐Step Tunneling Mechanism in Molecular Junctions Subject to Mechanical Stretching. Issue 7 (29th May 2022) - Bâldea, Ioan
Abstract: It is shown that the conductance G of molecular tunnel junctions wherein the charge transport is dominated by a single energy level can be expressed in closed analytic form which is exact and valid at arbitrary temperature T and model parameter values. On this basis, it is shown that the single‐step tunneling mechanism is compatible with a continuous thermal transition from a weakly T ‐dependent G at low T (Sommerfeld regime) to a nearly exponential 1 / T $1/T$ ‐dependent G at high T (Arrhenius‐like regime). This Sommerfeld–Arrhenius transition can be observed in real molecular junctions and can be continuously tuned, for example, via mechanical stretching. Abstract : The exact formula expressing the conductance of a tunneling junction as a function of temperature T deduced here in closed analytic form in terms of elementary function predicts a thermal transition from a nearly independent T (Sommerfeld) regime to a nearly exponential (Arrhenius) regime that can be continuously tuned, for example, via mechanical stretching or molecular orbital gating.